A fence-type stainless steel-based composite anode plate for copper electrowinning and a preparation method thereof
By adopting fence-type stainless steel composite anode plate for copper electrostatic accumulation, the problems of high energy consumption and environmental pollution in the prior art are solved, and the effects of low trough voltage, high current density and long service life are achieved.
Patent Information
- Application Number
- CN202010961643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-09-14
AI Technical Summary
The existing copper electroplastic technology has problems of high energy consumption and environmental pollution, especially when increasing the current density, which will lead to an increase in the tank voltage, coarse cathode copper particles and accelerated anode corrosion.
The fence-type stainless steel-based composite anode plate for copper electrostatic accumulation is used. The anode plate consists of conductive beams, fence-type anode plate brackets, fixing frames, insulating sheaths and insulators. The conductive beam consists of stainless steel tubes, copper layers and lead alloy layers. The anode composite rod is composed of stainless steel tubes, nickel layers, copper tin alloy layers and high calcium lead alloy layers, and an α-PbO2/active sponge titanium particles composite layer is electrodeposited on the surface.
It achieves low trough voltage, high current density and long service life, improves current conduction efficiency, and reduces energy consumption and environmental pollution.
Smart Images

Figure CN111893518B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper electrowinning, and in particular to a fence-type stainless steel-based composite anode plate for copper electrowinning and a preparation method thereof. Background Art
[0002] Energy consumption and environmental impact are two major concerns for future electrolytic copper technology. Electrolytic facilities will move to low-energy production processes and eliminate the production of these hazardous / harmful byproducts. To address these issues, scientists are working to develop high-performance anode materials and study alternative anode reactions. The use of lead alloy anodes opens up new areas for improvement in electrolytic technology from an energy and environmental perspective.
[0003] The full wet process of copper production requires a large amount of lead alloy anodes. At present, the current density of wet copper electrowinning is generally 200-260A / m 2 Within the range, the electrolysis cycle is 7 to 10 days. Every 10,000 tons of copper produced requires 3,000 to 4,000 anode plates, and a large number of electrolytic cells and stainless steel cathode plates are also required. The one-time investment is large and the recovery cycle is long. Under the existing conditions, increasing the current density is one of the effective ways to increase the output of electrolytic copper. However, the increase in current density will cause concentration polarization, resulting in an increase in the cell voltage, and cause the cathode copper particles to become coarser, the anode corrosion rate to accelerate, and the lead ion content in the solution to increase. Therefore, when increasing the current density, it is necessary to increase the electrolyte circulation speed, appropriately adjust the additives, and change the anode plate structure.
[0004] At present, the lead alloy anode used in industry can form an oxide film protective layer during the electrolysis process and has a relatively high safety guarantee in production, but the corrosion of the oxide layer on the surface of the anode will produce harmful substances in the electrolytic cell and pollute the cathode. In addition, the lead alloy anode needs an additional potential of 600mV to combine with oxygen to form a lead oxide layer on its surface during the electrolysis process, which will consume 30% of the electricity of each electrolytic cell. In order to solve the environmental problems and energy consumption problems caused by electrolytic copper, higher performance anode substitutes have been developed. For example:
[0005] Lead-based anode plate: The efforts made by enterprises on the anode plate node are concentrated on the addition of elements such as silver, calcium, strontium, cobalt, rare earth, as well as plate shape and plate rolling technology, to increase its metal hardness and crystal density. Although there is an effect of saving electricity, the poor conductivity of the lead alloy matrix itself, easy bending and deformation, and easy contamination of cathode products are inevitable.
[0006] Coated titanium anode: This type of anode is a titanium electrode coated with a layer of precious metal oxide (such as RuO2 or IrO2) on the surface. Its advantages are low energy consumption (10% to 17%), which can not only avoid the deposition of lead in the electrolytic cell and the contamination of the cathode product, but also does not require the addition of cobalt sulfate; but the main disadvantages of this anode are that its service life is too short and the material cost is too high.
[0007] The anode is made of light metal aluminum as the inner core and lead alloy as the outer layer through melting or electroplating. There are some difficult problems to solve. First, the fluidity of the lead alloy liquid and the possible holes in the large-sized anode plate cannot be solved. Second, some grain boundary gaps will appear in the coating. The oxygen produced during electrolysis will pass through the grain boundary gaps of the coating to oxidize the aluminum matrix and form an aluminum oxide film with poor conductivity, which will deteriorate the anode performance.
[0008] Fence-type anode plate for non-ferrous metal electrowinning: Improves the flowability of electrolyte, improves the effect and quality of electrolytic non-ferrous metal collection, and avoids the defect of cathode plate touching anode plate when lifting. Using cheap aluminum rod as the matrix, the material cost is significantly reduced, but there are still disadvantages of interface resistance, short life, low strength and high cell voltage.
[0009] Since the active layer of the traditional anode β-PbO2 has low adhesion on the lead substrate and is easy to peel off, it is easy to contaminate the cathode product during the electrolysis process. α-PbO2 is closely combined with the lead substrate, but α-PbO2 has a low overpotential for oxygen evolution as an anode, high porosity, and poor corrosion resistance, so it cannot be used alone as an anode. By adding particles to composite electrodeposition, a coating without internal stress can be produced, and it has good density and can be used for a long time at high current density.
[0010] Therefore, it is necessary to further develop an anode with high current efficiency, low energy consumption, high strength, long-term use under high current density, and high cathode copper product quality (less lead). Summary of the invention
[0011] In view of this, the object of the present invention is to provide a fence-type stainless steel-based composite anode plate for copper electrowinning and a preparation method thereof. The composite anode plate provided by the present invention has the advantages of good electrocatalytic activity, low cell voltage, long service life, high service current density, high electrical efficiency and strength.
[0012] The present invention provides a fence-type stainless steel-based composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator;
[0013] The conductive beam is composed of a stainless steel tube, a copper layer disposed on the surface of the stainless steel tube, and a first lead alloy layer disposed on the surface of the copper layer;
[0014] The fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube, and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer;
[0015] The fixing frame is made of lead or lead alloy, and is vertically connected to the fence-type anode plate support to fix the anode composite rod of the fence-type anode plate support;
[0016] The insulating sheath is arranged parallel to the edge side of the fence type anode plate support to fix the edge of the fence type anode plate support;
[0017] The insulator is arranged at the lower part of the fence type anode plate support and is used for fixing the lower part of the fence type anode plate support.
[0018] Preferably, the first lead alloy layer comprises a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer which are stacked in sequence, the lead-tin-antimony rare earth alloy layer is close to the surface end of the copper layer; the lead-tin-antimony rare earth alloy layer has a thickness of 8 to 100 μm, and the first lead alloy layer has a thickness of 0.1 to 10 mm;
[0019] The second lead alloy layer includes a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer which are stacked in sequence, the nickel layer is close to the surface end of the stainless steel pipe; the thickness of the nickel layer is 6 to 10 μm, the thickness of the copper-tin alloy layer is 60 to 200 μm; the thickness of the second lead alloy layer is 1 to 6 mm.
[0020] Preferably, the high calcium lead alloy in the high calcium lead alloy layer is selected from one of lead calcium alloy, lead calcium tin alloy, lead calcium tin rare earth alloy, lead calcium tin aluminum rare earth alloy and lead calcium silver tin rare earth alloy; the mass percentage of calcium in the high calcium lead alloy is 0.1 to 5wt%.
[0021] Preferably, the content of tin in the lead-tin-antimony rare earth alloy layer is 1-7wt%, the content of antimony is 0.5-3wt%, the content of rare earth is 0.001-0.08wt%, and the balance is lead.
[0022] Preferably, the shape of the active titanium sponge particles in the α-PbO2 / active titanium sponge particle composite layer is cone-shaped or rod-shaped; the particle size of the active titanium sponge particles is 0.1 to 10 μm; and the content of the active titanium sponge particles in the composite layer is 0.5 to 10 wt%.
[0023] Preferably, in the conductive beam and the anode composite rod, the outer surface of the stainless steel tube has a thread, and the depth of the thread is 0.3 to 1.2 mm; the cross-section of the stainless steel tube is a hollow isomeric circular shape, a hollow isomeric square shape, a hollow isomeric rectangular shape or a hollow elliptical shape; the long axis length of the inner wall of the cross-section of the stainless steel tube is 2 to 20 mm, and the short axis length is 1 to 8 mm; the material of the stainless steel tube is 304 stainless steel or 316L stainless steel; the tube thickness of the stainless steel tube is 2 to 6 mm.
[0024] Preferably, the insulating sheath and the insulator are made of modified PE-PP, modified PVC-PP or modified ABS-PP;
[0025] The material of the fixing frame is selected from one of lead-tin-antimony alloy, lead-tin-antimony rare earth alloy and lead-tin-antimony-strontium rare earth alloy.
[0026] The present invention provides a method for preparing a fence-type stainless steel-based composite anode plate for copper electrowinning as described in the above technical solution, comprising the following steps:
[0027] A) activating a stainless steel tube, then coating a copper layer on the surface of the activated stainless steel tube, then activating the copper layer, and then coating a first lead alloy layer on the surface of the activated copper layer to obtain a conductive beam;
[0028] B) activating the stainless steel tube, coating the outer surface of the activated stainless steel tube with a second lead alloy layer, and then electrodepositing an α-PbO2 / active titanium sponge particle composite layer on the surface of the second lead alloy layer to obtain an anode composite rod;
[0029] Assembling a plurality of the anode composite rods into a fence shape to obtain a fence-shaped anode plate support;
[0030] The anode composite rods of the fence-type anode plate support are fixed by a fixing frame, and the edge side of the fence-type anode plate support is fixed by an insulating sheath to obtain an integral fence-type anode plate support;
[0031] There is no order of precedence between step A) and step B);
[0032] C) connecting the conductive beam obtained in step A) with the integral fence-type anode plate support obtained in step B), and installing an insulator at the bottom of the fence-type anode plate support to obtain a fence-type stainless steel-based composite anode plate for copper electrodeposition.
[0033] Preferably, in step A), the coating process of the first lead alloy layer specifically includes:
[0034] Placing the activated copper-clad stainless steel tube in a lead-tin-antimony rare earth alloy liquid for hot-dip plating; the temperature of the lead-tin-antimony rare earth alloy liquid is 400-600° C., and the hot-dip plating time is 0.1-8 min;
[0035] Placing the hot-dip plated copper-clad stainless steel tube in a die-casting mold, pouring antimony-containing lead alloy liquid and die-casting to obtain a first lead alloy layer;
[0036] In step B), the coating process of the second lead alloy layer specifically includes:
[0037] The activated stainless steel tube is placed in a nickel plating solution for electroplating; the nickel plating solution comprises: 180-250 g / L nickel chloride, 80-120 ml / L hydrochloric acid, and 8-20 g / L disodium ethylenediaminetetraacetate; the cathode current density of the electroplating is 2-5 A / dm 2 The electroplating temperature is 25 to 45° C., and the electroplating time is 1 to 20 minutes;
[0038] The nickel-plated stainless steel tube is placed in a copper-tin alloy plating solution for secondary electroplating; the copper-tin alloy plating solution comprises: 150-200 g / L potassium pyrophosphate, 10-30 g / L copper pyrophosphate, 8-20 g / L sodium stannate, 30-60 g / L potassium sodium tartrate, and 0.005-0.02 g / L PVP; the cathode current density of the secondary electroplating is 1-3 A / dm 2 The temperature of the secondary electroplating is 20 to 50° C., and the time of the secondary electroplating is 20 to 60 minutes;
[0039] The copper-tin alloy-plated stainless steel tube is placed in a drawing and extrusion machine, and the semi-molten high-calcium lead alloy is coated by drawing and extrusion, and then cooled to obtain a second lead alloy layer.
[0040] Preferably, in step B), the preparation process of the α-PbO2 / active titanium sponge particle composite layer specifically includes:
[0041] The stainless steel tube wrapped with the second lead alloy layer is placed in an alkaline lead solution for electrodeposition to obtain an α-PbO2 / active sponge titanium particle composite layer; the alkaline lead solution comprises: 40-60 g / L lead oxide, 100-180 g / L sodium hydroxide, 10-40 g / L tartaric acid, 0.1-10 g / L potassium dichromate, 0.01-0.5 g / L surfactant, and 2-10 g / L active sponge titanium particles; the anode current density of the electrodeposition is 1-3 A / dm 2 , the electrodeposition temperature is 20 to 50° C., and the electrodeposition time is 0.5 to 3 hours;
[0042] The active titanium sponge particles are prepared according to the following steps:
[0043] The sponge titanium particles are placed in a hydrochloric acid solution for activation, and then the activated sponge titanium particles are placed in an active substance solution for ultrasonic dispersion, filtration, drying, and sintering to obtain active sponge titanium particles; the concentration of the hydrochloric acid solution is 15-25wt%; the activation temperature is 60-80°C, and the activation time is 5-30min; the active substance solution contains active metal compounds, citric acid and ethylene glycol, the active metal compounds include ruthenium chloride, stannous chloride and cobalt chloride, and the molar ratio of the ruthenium chloride, stannous chloride and cobalt chloride is The molar ratio of the active metal compound, citric acid and ethylene glycol is (1-5): (3-8): (10-30); the ultrasonic dispersion time is 0.5-2h; the drying temperature is 100-150°C, and the drying time is ≥10min; the sintering temperature is 400-600°C, and the sintering time is 5-50min; the ruthenium oxide loading on the surface of the active titanium sponge particles is 1-3g / m 2 .
[0044] Compared with the prior art, the present invention provides a fence-type stainless steel-based composite anode plate for copper electrodeposition and a preparation method thereof. The composite anode plate provided by the present invention comprises a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator; the conductive beam is composed of a stainless steel tube, a copper layer arranged on the surface of the stainless steel tube and a first lead alloy layer arranged on the surface of the copper layer; the fence-type anode plate bracket is vertically connected to the conductive beam; the fence-type anode plate bracket is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer; the fixing frame is made of lead or lead alloy, which is vertically connected to the fence-type anode plate bracket to fix the anode composite rod of the fence-type anode plate bracket; the insulating sheath is arranged in parallel to the edge side of the fence-type anode plate bracket to fix the edge of the fence-type anode plate bracket; the insulator is arranged at the lower part of the fence-type anode plate bracket to fix the lower part of the fence-type anode plate bracket. The fence-type stainless steel-based composite anode plate for copper electrowinning has at least the following advantages: 1) The stainless steel tube is used as the matrix and connected with the conductive copper-clad stainless steel tube to form an integral anode plate structure, which greatly reduces the resistance of the anode plate, improves the conduction efficiency of the anode plate, significantly reduces the cell voltage, and rapidly increases the current efficiency. 2) The thermal conductivity of stainless steel is not much different from that of lead alloy. During the electrolysis process, stainless steel-based lead alloy is less likely to fall off than aluminum-based or copper-based lead alloy materials. 3) The fence-type hollow stainless steel-based composite material is used, which greatly reduces the amount of materials used and reduces the cost of the anode plate by more than 30%. 4) The stainless steel base increases the hardness and strength of the anode plate, ensuring the stability of the external dimensions of the anode plate and the conductive beam. 5) The outer surface of the stainless steel tube is provided with threads (tapping), which is not only conducive to enhancing the bite force between the stainless steel tube and the lead alloy layer, but also increases the conductive cross-sectional area of the lead alloy layer, thereby increasing the conduction efficiency of the plate. 6) Water circulation or air circulation cooling can be used in the stainless steel tube to effectively control the heating temperature of the anode plate during electrolysis, reduce the cell voltage, reduce power consumption, and improve the electrolysis efficiency. 7) By adding a small amount of rare earth, the melting temperature of the lead-tin-antimony rare earth alloy layer and the antimony-containing lead alloy is not much different, so that the stainless steel / lead-tin-antimony rare earth alloy / antimony-containing lead alloy can be easily formed into a gradient metallurgical bond; and by introducing nickel and copper-tin alloy between stainless steel and high-calcium lead alloy, the bonding strength of the composite material is greatly improved. 8) High-calcium lead alloy is used as the intermediate layer. Because calcium is conducive to the formation of α-PbO2, the lead alloy and the α-PbO2 / active sponge titanium particle composite layer are more closely combined, which protects the corrosion of lead and improves the life of the anode. 9) In the active sponge titanium particles, the active metal oxide particles are adsorbed on the surface of the sponge titanium particles, which greatly improves the oxygen evolution activity of the composite layer and reduces the cell voltage during the use of the electrode.
[0045] Experimental results show that compared with the traditional Pb-0.06wt%Ca-1.2wt%Sn anode, when the composite anode plate provided by the present invention is used for copper electroplating, the cell voltage can be reduced by 400mV, the service life is extended by 3 times, the current conduction efficiency is increased by more than 4-5%, and the current density can be increased to more than 2 times the original. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0047] Figure 1 It is a schematic structural diagram of a fence-type stainless steel-based composite anode plate for copper electrodeposition provided by the present invention;
[0048] Figure 2 yes Figure 1 AA cross-sectional diagram of ;
[0049] Figure 3 yes Figure 1 BB cross-section diagram;
[0050] Figure 4 yes Figure 1 Cross-section of the anode composite rod;
[0051] Figure 5 It is a schematic diagram of the insulator structure provided by the present invention. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The invention provides a fence-type stainless steel-based composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator.
[0054] See also Figures 1 to 5 , Figure 1 It is a schematic diagram of the structure of a fence-type stainless steel-based composite anode plate for copper electrowinning provided by the present invention. Figure 2 yes Figure 1 AA cross-sectional diagram of Figure 3 yes Figure 1 BB cross-section diagram, Figure 4 yes Figure 1 Cross-section of the anode composite rod. Figure 5 It is a schematic diagram of the insulator structure provided by the present invention; in the figure, 1 is the remaining part of the conductive beam except the first lead alloy layer (i.e., copper-clad stainless steel tube), 2 is the first lead alloy layer, 3 is the anode composite rod, 4 is the fixing frame, 5 is the insulating sheath, 6 is the α-PbO2 / active sponge titanium particle composite layer, 7 is the insulator, 1-1 is the conductive beam stainless steel tube, 1-2 is the copper layer, 3-1 is the anode composite rod stainless steel tube, 3-2 is the nickel layer, 3-3 is the copper-tin alloy layer, and 3-4 is the high calcium lead alloy layer.
[0055] In the composite anode plate provided by the present invention, the conductive beam is composed of a stainless steel tube, a copper layer arranged on the surface of the stainless steel tube, and a first lead alloy layer arranged on the surface of the copper layer. The outer surface of the stainless steel tube preferably has threads, and the depth of the threads is preferably 0.3-1.2 mm, specifically 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm or 1.2 mm; the cross section of the stainless steel tube is preferably a hollow isomeric circular, hollow isomeric square, hollow isomeric rectangular or hollow elliptical; the major axis length of the inner wall of the cross section of the stainless steel tube is preferably 2-20 mm, specifically 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm m, 15mm, 16mm, 17mm, 18mm, 19mm, 20mm; the minor axis length of the inner wall of the cross section of the stainless steel tube is preferably 1-8mm, specifically 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.5mm, 6mm, 6.5mm, 7mm, 7.5mm or 8mm; the material of the stainless steel tube is preferably 304 stainless steel or 316L stainless steel; the tube thickness of the stainless steel tube is preferably 2-6mm, specifically 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.5mm or 6mm.
[0056] In the composite anode plate provided by the present invention, in the conductive beam, the thickness of the copper layer is preferably 2 to 8 mm, specifically 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm or 8 mm.
[0057] In the composite anode plate provided by the present invention, in the conductive beam, the first lead alloy layer preferably includes a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer stacked in sequence, and the lead-tin-antimony rare earth alloy layer is close to the surface end of the copper layer. The content of tin in the lead-tin-antimony rare earth alloy layer is preferably 1-7wt%, specifically 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt% or 7wt%; the content of antimony in the lead-tin-antimony rare earth alloy layer is preferably 0.5-3wt%, specifically 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt%, 2wt%, 2.3wt%, 2.5wt%, 2.7wt% or 3wt%; the type of rare earth in the lead-tin-antimony rare earth alloy layer includes but is not limited to one or more of neodymium (Nd), cerium (Ce), lanthanum (La), praseodymium (Pr), samarium (Sm) and terbium (Tb). The content of lead in the lead-tin-antimony rare earth alloy layer is the remainder; the thickness of the lead-tin-antimony rare earth alloy layer is preferably 8-100μm, specifically 8μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm.In the present invention, the composition of the antimony-containing lead alloy layer is an antimony-containing lead alloy, and the antimony-containing lead alloy includes but is not limited to Pb-Sn-Sb, Pb-Sb, Pb-Ag-Sn-Sb or Pb-Ag-Sn-Sb-rare earth; the Sn content in the Pb-Sn-Sb is preferably 0.5-2wt%, specifically 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%, the Sb content is preferably 1-5wt%, specifically 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, and the balance is Pb; the Sn content in the Pb-Ag-Sn-Sb is preferably 0.1 % , 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt% or 1.5wt%; the Sb content is preferably 2-6wt%, specifically 2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%; the Ag content is preferably 0.01-0.1wt%, specifically 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt% or 0.1wt%; and the balance is Pb. In the present invention, the thickness of the first lead alloy layer is 0.1-10 mm, specifically 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0058] In the composite anode plate provided by the present invention, the fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer disposed on the surface of the stainless steel tube, and an α-PbO2 / active sponge titanium particle composite layer disposed on the surface of the second lead alloy layer. The specification parameters of the stainless steel tube can refer to the stainless steel tube in the conductive beam introduced above, and will not be repeated here.
[0059] In the composite anode plate provided by the present invention, in the composite anode rod, the second lead alloy layer preferably includes a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer stacked in sequence, and the nickel layer is close to the surface end of the stainless steel pipe. Wherein, the composition of the high-calcium lead alloy layer is a high-calcium lead alloy, and the high-calcium lead alloy is selected from one of lead-calcium alloy, lead-calcium-tin alloy, lead-calcium-tin rare earth alloy, lead-calcium-tin aluminum rare earth alloy and lead-calcium-tin silver rare earth alloy, and the mass percentage of calcium in the high-calcium lead alloy is preferably 0.1-5wt%, specifically 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%. In some embodiments provided by the present invention, the high-calcium lead alloy is specifically selected from a lead-calcium-tin alloy, and the calcium content in the lead-calcium-tin alloy is preferably 0.1-5wt%, specifically 0.1wt%, 0.8wt% or 5wt%, and the tin content in the lead-calcium-tin alloy is preferably 0.5-3wt%, specifically 1wt%, 1.5wt% or 1.8wt%, and the balance is lead. In the present invention, the thickness of the nickel layer is preferably 6-10μm, specifically 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm; the thickness of the copper-tin alloy layer is preferably 60-200μm, specifically 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm; the thickness of the second lead alloy layer is preferably 1-6mm, specifically 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.5mm or 6mm.
[0060] In the composite anode plate provided by the present invention, in the anode composite rod, the components of the α-PbO2 / active sponge titanium particles composite layer are α-PbO2 and active sponge titanium particles. The active sponge titanium particles include sponge titanium particles and active metal oxides loaded on the surface of the sponge titanium particles; the active metal oxides preferably include ruthenium oxide, tin oxide and cobalt oxide, and the molar ratio of ruthenium oxide, tin oxide and cobalt oxide is preferably (10-30): (30-50): (10-30), specifically 20:50:30 or 30:40:30; the ruthenium oxide loading on the surface of the active sponge titanium particles is preferably 1-3 g / m 2 , specifically 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 or 3g / m2 . In the present invention, the shape of the active titanium sponge particles may be cone-shaped or rod-shaped; the particle size of the active titanium sponge particles is preferably 0.1-10 μm, specifically 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the content of the active titanium sponge particles in the composite layer is preferably 0.5-10 wt%, specifically 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%. In the present invention, the thickness of the α-PbO2 / active sponge titanium particle composite layer is preferably 50-500 μm, more preferably 200 μm, specifically 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm.
[0061] In the composite anode plate provided by the present invention, in the fence-type anode plate support, the cross-sectional structure of the anode composite rod can be selected as follows: Figure 4 Any of the 5 structures shown.
[0062] In the composite anode plate provided by the present invention, the material of the fixing frame is lead or lead alloy, and the lead alloy is preferably one of lead-tin-bismuth alloy, lead-tin-antimony alloy, lead-tin-antimony rare earth alloy and lead-tin-antimony-strontium rare earth alloy; the tin content in the lead-tin-bismuth alloy is preferably 0.5-5wt%, specifically 0.25wt%, the bismuth content in the lead-tin-bismuth alloy is preferably 0.2-3wt%, specifically 1.5wt%, and the balance is lead; the tin content in the lead-tin-antimony alloy is preferably 0.1-1wt%, specifically 0.6 wt%, the antimony content in the lead-tin-antimony alloy is preferably 0.5-1.5wt%, specifically 0.8wt%, and the balance is lead; the tin content in the lead-tin-antimony rare earth alloy is preferably 0.1-1wt%, specifically 0.5wt%, the antimony content in the lead-tin-antimony rare earth alloy is preferably 0.5-1.5wt%, specifically 0.8wt%, the rare earth in the lead-tin-antimony rare earth alloy is preferably cerium, the rare earth content is preferably 0.01-0.1wt%, specifically 0.06wt%, and the balance is lead. In the present invention, the fixing frame is vertically connected to the fence-type anode plate bracket to fix the anode composite rod of the fence-type anode plate bracket.
[0063] In the composite anode plate provided by the present invention, the material of the insulating sheath and the insulator is preferably modified PE-PP, modified PVC-PP or modified ABS-PP; the insulating sheath is arranged parallel to the edge side of the fence type anode plate bracket to fix the edge of the fence type anode plate bracket; the insulator is arranged at the lower part of the fence type anode plate bracket to fix the lower part of the fence type anode plate bracket.
[0064] The present invention also provides a method for preparing the fence-type stainless steel-based composite anode plate for copper electrowinning described in the above technical solution, comprising the following steps:
[0065] A) activating a stainless steel tube, then coating a copper layer on the surface of the activated stainless steel tube, then activating the copper layer, and then coating a first lead alloy layer on the surface of the activated copper layer to obtain a conductive beam;
[0066] B) activating the stainless steel tube, coating the outer surface of the activated stainless steel tube with a second lead alloy layer, and then electrodepositing an α-PbO2 / active titanium sponge particle composite layer on the surface of the second lead alloy layer to obtain an anode composite rod;
[0067] Assembling a plurality of the anode composite rods into a fence shape to obtain a fence-shaped anode plate support;
[0068] The anode composite rods of the fence-type anode plate support are fixed by a fixing frame, and the edge side of the fence-type anode plate support is fixed by an insulating sheath to obtain an integral fence-type anode plate support;
[0069] There is no order of precedence between step A) and step B);
[0070] C) connecting the conductive beam obtained in step A) with the integral fence-type anode plate support obtained in step B), and installing an insulator at the bottom of the fence-type anode plate support to obtain a fence-type stainless steel-based composite anode plate for copper electrodeposition.
[0071] In the preparation method provided by the present invention, in step A), the stainless steel tube is preferably cleaned before and after the activation treatment; the stainless steel tube is preferably activated in a hydrochloric acid solution, the concentration of the hydrochloric acid solution is preferably 5-20wt%, specifically 5wt%, 10wt%, 15wt% or 20wt%, the temperature of the activation treatment is preferably 15-35°C, specifically 15°C, 20°C, 25°C, 30°C or 35°C, the time of the activation treatment is preferably 0.5-2min, specifically 0.5min, 1min, 1.5min or 2min; the copper layer is preferably also activated before coating, the copper layer is preferably activated in a nitric acid solution, the concentration of the nitric acid is preferably 2-10wt%, specifically 2wt%, 5wt%, 7wt% or 10wt%, the temperature of the activation treatment is preferably 20-70°C, specifically 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55 ℃, 60℃, 65℃ or 70℃, the activation treatment time is preferably 0.5-10min, specifically 0.5min, 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min; after the copper layer is coated on the surface of the stainless steel pipe, it is preferably processed into a U-shaped beam structure; the coated copper layer is preferably cleaned before and after the activation treatment; the coated copper layer is preferably activated in a nitric acid solution, the concentration of nitric acid is preferably 10-25wt%, specifically 10wt%, 15wt%, 20wt% or 25wt%, the activation treatment temperature is preferably 40-80℃, specifically 40℃, 50℃, 60℃, 70℃ or 80℃, the activation treatment time is preferably 1-5min, specifically 1min, 1.5min, 2min, 2.5min, 3min, 3.5min, 4min, 4.5min or 5min.
[0072] In the preparation method provided by the present invention, in step A), the coating process of the first lead alloy layer preferably includes:
[0073] Placing the activated copper-clad stainless steel tube in a lead-tin-antimony rare earth alloy liquid for hot-dip plating; wherein the temperature of the lead-tin-antimony rare earth alloy liquid is preferably 400-600°C, specifically 400°C, 450°C, 500°C, 550°C or 600°C; the hot-dip plating time is preferably 0.1-8min, specifically 0.1min, 0.5min, 1min, 2min, 3min, 4min, 5min, 6min, 7min or 8min; during the hot-dip plating process, the stainless steel tube is preferably moved up and down; in order to ensure that the thickness of the lead-tin-antimony rare earth alloy layer formed after hot-dip plating meets the requirements, the hot-dip plating is preferably repeated 2-4 times;
[0074] The hot-dip-plated copper-clad stainless steel tube is placed in a die-casting mold, and antimony-lead alloy liquid is poured and die-casted to obtain a first lead alloy layer.
[0075] In the preparation method provided by the present invention, in step B), the stainless steel tube is preferably cleaned before and after the activation treatment; the stainless steel tube is preferably activated in a hydrochloric acid solution, the concentration of the hydrochloric acid solution is preferably 2-20wt%, specifically 2wt%, 5wt%, 7wt%, 10wt%, 15wt% or 20wt%, the temperature of the activation treatment is preferably 20-40°C, specifically 20°C, 25°C, 30°C, 35°C or 40°C, the time of the activation treatment is preferably 1-5min, specifically 1min, 1.5min, 2min, 2.5min, 3min, 3.5min, 4min, 4.5min or 5min.
[0076] In the preparation method provided by the present invention, in step B), the coating process of the second lead alloy layer preferably includes:
[0077] The stainless steel tube after activation treatment is placed in a nickel plating solution for electroplating; wherein the components of the nickel plating solution preferably include nickel chloride, hydrochloric acid, disodium ethylenediaminetetraacetate and water, the content of the nickel chloride is preferably 180-250 g / L, specifically 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L or 250 g / L, the concentration of the hydrochloric acid is preferably 30-40 wt%, specifically 37 wt%, the content of the hydrochloric acid is preferably 80-120 mL / L, specifically 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L or 250 g / L The electroplating temperature is 80 mL / L, 85 mL / L, 90 mL / L, 95 mL / L, 100 mL / L, 105 mL / L, 110 mL / L, 115 mL / L or 120 mL / L, the content of disodium edetate is preferably 8-20 g / L, specifically 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L; the cathode current density of the electroplating is preferably 2-5 A / dm 2 , specifically 2A / dm 2 , 2.5A / dm 2 、3A / dm 2 、3.5A / dm 2 , 4A / dm 2 , 4.5A / dm 2 or 5A / dm 2; The electroplating temperature is preferably 25-45°C, specifically 25°C, 30°C, 35°C, 40°C or 45°C; the electroplating time is preferably 1-20min, specifically 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min or 20min; after the electroplating is completed, cleaning is performed;
[0078] The nickel-plated stainless steel tube is placed in a copper-tin alloy plating solution for secondary electroplating; wherein the copper-tin alloy plating solution comprises potassium pyrophosphate, copper pyrophosphate, sodium stannate, potassium sodium tartrate, PVP and water, the content of potassium pyrophosphate is preferably 150-200 g / L, specifically 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L or 200 g / L, the content of copper pyrophosphate is preferably 10-30 g / L, specifically 10 g / L, 15 g / L, 20 g / L, 25 g / L or 30 g / L, the content of sodium stannate is preferably The content of potassium sodium tartrate is preferably 30-60 g / L, specifically 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L, the content of PVP is preferably 0.005-0.02 g / L, specifically 0.005 g / L, 0.01 g / L, 0.015 g / L or 0.02 g / L; the cathode current density of the secondary electroplating is preferably 1-3 A / dm 2 , specifically 1A / dm 2 , 1.5A / dm 2 , 2A / dm 2 , 2.5A / dm 2 or 3A / dm 2 ; The temperature of the secondary electroplating is preferably 20-50°C, specifically 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C; The time of the secondary electroplating is preferably 20-60min, specifically 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min; After the secondary electroplating, washing and drying are performed;
[0079] The copper-tin alloy-plated stainless steel tube is placed in a drawing and extrusion machine, and the semi-molten high-calcium lead alloy is coated by drawing and extrusion, and then cooled to obtain a second lead alloy layer.
[0080] In the preparation method provided by the present invention, in step B), the preparation process of the α-PbO2 / active titanium sponge particle composite layer preferably includes:
[0081] The stainless steel tube wrapped with the second lead alloy layer is placed in an alkaline lead solution for electrodeposition to obtain an α-PbO2 / active sponge titanium particle composite layer. Wherein, the components of the alkaline lead liquid include lead oxide, sodium hydroxide, tartaric acid, potassium dichromate, a surfactant, active sponge titanium particles and water. The content of the lead oxide is preferably 40-60 g / L, specifically 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L. The content of the sodium hydroxide is preferably 100-180 g / L, specifically 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L or 180 g / L. The content of the tartaric acid is preferably 10-40 g / L, specifically 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L or 40 g / L. The content of the potassium dichromate is preferably 0.1-10 g / L, specifically 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L or 40 g / L. The content of the active titanium sponge particles is preferably 2-10 g / L, and specifically can be 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L. The type of the surfactant includes one or more of OP emulsifier, PVP and gelatin. The content of the surfactant is preferably 0.01-0.5 g / L, and specifically can be 0.01 g / L, 0.05 g / L, 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.25 g / L, 0.3 g / L, 0.35 g / L, 0.4 g / L, 0.45 g / L or 0.5 g / L. The content of the active titanium sponge particles is preferably 2-10 g / L, and specifically can be 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L. The anode current density of the electrodeposition is preferably 1-3 A / dm 2 , specifically 1A / dm 2 , 1.5A / dm 2 , 2A / dm 2 , 2.5A / dm 2 or 3A / dm 2 ; The temperature of the electroplating is preferably 20-50°C, specifically 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C; the time of the electroplating is preferably 0.5-3h, specifically 0.5h, 1h, 1.5h, 2h, 2.5h or 3h.
[0082] In the preparation method provided by the present invention, in step B), the active titanium sponge particles are prepared according to the following steps:
[0083] The sponge titanium particles are placed in a hydrochloric acid solution for activation, and then the activated sponge titanium particles are placed in an active substance solution for ultrasonic dispersion, filtration, drying, and sintering to obtain active sponge titanium particles. Wherein, before the sponge titanium particles are activated, they are preferably cleaned first; the concentration of the hydrochloric acid solution is preferably 15-25wt%, specifically 15wt%, 20wt% or 25wt%; the activation temperature is preferably 60-80°C, specifically 60°C, 65°C, 70°C, 75°C or 80°C; the activation time is preferably 5-30min, specifically 5min, 10min, 15min, 20min, 25min or 30min; the active substance solution contains active metal compounds, citric acid and ethylene glycol, the active metal compounds preferably include ruthenium chloride, stannous chloride and cobalt chloride, the molar ratio of ruthenium chloride, stannous chloride and cobalt chloride is preferably (10-30): (30-50): (10-30), specifically 20:50:30 or 30:40:30; the molar ratio of the active metal compound, citric acid and ethylene glycol is preferably (10-30): (30-50): (10-30), specifically 20:50:30 or 30:40:30. Preferably, it is (1-5): (3-8): (10-30), specifically 2:3:10 or 5:6:20; the ultrasonic dispersion time is preferably 0.5-2h, specifically 0.5h, 1h, 1.5h or 2h; the drying temperature is preferably 100-150°C, specifically 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the drying time is preferably ≥10min; the sintering temperature is preferably 400-600°C, specifically 400°C, 450°C, 500°C, 550°C or 600°C; the sintering time is preferably 5-50min, and can be 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min or 50min; the ruthenium oxide loading on the surface of the active sponge titanium particles is preferably 1-3g / m 2 , specifically 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 or 3g / m 2 ; In order to ensure that the active metal oxide loading on the surface of the finally prepared active sponge titanium particles meets the requirements, it is preferred to repeat "placing in active material solution for ultrasonic dispersion, filtering, drying, and sintering" 8 to 10 times, and the last sintering time is preferably 0.5h.
[0084] In the preparation method provided by the present invention, in step C), the conductive beam is preferably connected to the integral fence-type anode plate support by welding.
[0085] The fence-type stainless steel-based composite anode plate for copper electrowinning provided by the present invention and the preparation method thereof have at least the following advantages:
[0086] 1) The stainless steel tube is used as the substrate and connected with the conductive copper-clad stainless steel tube to form an integral anode plate structure, which greatly reduces the resistance of the anode plate, improves the conduction efficiency of the anode plate, significantly reduces the cell voltage, and rapidly increases the current efficiency.
[0087] 2) The thermal conductivity of stainless steel is not much different from that of lead alloy. During the electrolysis process, stainless steel-based lead alloy is less likely to fall off than aluminum-based or copper-based lead alloy materials.
[0088] 3) The use of fence-type hollow stainless steel-based composite materials greatly reduces the amount of materials used and reduces the cost of the anode plate by more than 30%.
[0089] 4) The stainless steel base increases the hardness and strength of the anode plate, ensuring the stability of the dimensions of the anode plate and the conductive beam.
[0090] 5) Setting threads (tapping) on the outer surface of the stainless steel tube not only helps to enhance the bite force between the stainless steel tube and the lead alloy layer, but also increases the conductive cross-sectional area of the lead alloy layer, thereby increasing the conduction efficiency of the electrode plate.
[0091] 6) Water circulation or air circulation cooling can be used in stainless steel pipes to effectively control the heating temperature of the anode plate during electrolysis, reduce the cell voltage, reduce power consumption, and improve electrolysis efficiency.
[0092] 7) A small amount of rare earth is added to the lead-tin-antimony rare earth alloy liquid to reduce the melting temperature of the lead alloy liquid, so that the melting temperature of the lead-tin-antimony rare earth alloy layer and the antimony-containing lead alloy are not much different, so as to achieve the purpose of easily forming a gradient metallurgical bonding of stainless steel / lead-tin-antimony rare earth alloy / antimony-containing lead alloy; and by introducing nickel and copper-tin alloy between stainless steel and high-calcium lead alloy, the bonding strength of the composite material is greatly improved.
[0093] 8) High calcium lead alloy is used as the middle layer. Since calcium is conducive to the formation of α-PbO2, the lead alloy and the α-PbO2 / active sponge titanium particle composite layer are more closely combined, which protects the lead from corrosion and increases the life of the anode.
[0094] 9) In the active titanium sponge particles, active metal oxide particles are adsorbed on the surface of the titanium sponge particles, which greatly improves the oxygen evolution activity of the composite layer and reduces the cell voltage during the use of the electrode.
[0095] Experimental results show that compared with the traditional Pb-0.06wt%Ca-1.2wt%Sn anode, when the composite anode plate provided by the present invention is used for copper electroplating, the cell voltage can be reduced by 400mV, the service life is extended by 3 times, the current conduction efficiency is increased by more than 4-5%, and the current density can be increased to more than 2 times the original.
[0096] For the purpose of greater clarity, the invention is described in detail through the following examples.
[0097] Example 1
[0098] This embodiment provides a fence-type stainless steel-based composite anode plate for copper electrowinning, including a conductive beam, a fence-type anode plate bracket, a lead or lead alloy fixing frame, an insulating sheath and an insulator; the structural schematic diagram of the composite anode plate for copper electrowinning in this embodiment is as follows Figure 1 As shown, 1 is a copper-clad stainless steel tube conductive beam, 2 is a first lead alloy layer, 3 is a fence-type anode plate composite rod, 4 is a lead or lead alloy fixing frame, 5 is an insulating sheath, and 7 is an insulator.
[0099] The conductive beam is composed of a stainless steel tube, a copper layer arranged on the surface of the stainless steel tube and a first lead alloy layer arranged on the surface of the copper layer; the fence type anode plate bracket is vertically connected to the conductive beam; the fence type anode plate bracket is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer; the fixing frame is vertically connected to the fence type anode plate bracket; the insulating sheath is arranged in parallel to the edge side of the fence type anode plate bracket; the insulator is arranged at the lower part of the fence type anode plate bracket to fix the lower part of the fence type anode plate bracket.
[0100] In this embodiment, the material of the stainless steel tube is 304, the outer surface of the stainless steel tube is tapped, the depth of the thread is 0.4mm, the cross section of the stainless steel tube is a hollow square; the long axis of the inner wall is 20mm, the short axis is 8mm, the tube thickness is 2mm; the thickness of the copper layer is 2mm;
[0101] In this embodiment, the first lead alloy layer is sequentially: a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer arranged on the surface of the copper-clad stainless steel tube; the thickness of the lead-tin-antimony rare earth alloy layer is 100 μm, the content of tin in the lead-tin-antimony rare earth alloy layer is 1wt%, the content of antimony is 3wt%, the content of rare earth samarium (Sm) is 0.08wt%, and the balance is lead; the thickness of the first lead alloy layer is 8mm; the lead alloy in the antimony-containing lead alloy layer is a lead-silver-tin-antimony alloy, the content of tin in the alloy layer is 0.6wt%, the content of antimony is 3.5wt%, the content of silver is 0.05wt%, and the balance is lead;
[0102] In this embodiment, the second lead alloy layer is sequentially: a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer arranged on the surface of the base stainless steel tube; the thickness of the nickel layer is 10 μm, the thickness of the copper-tin alloy layer is 200 μm, and the thickness of the second lead alloy layer is 6 mm; the high-calcium lead alloy in the high-calcium lead alloy layer is lead-calcium-tin, wherein the mass percentage of calcium in the high-calcium lead alloy is 5wt%, the mass percentage of tin in the high-calcium lead alloy is 1.5wt%, and the balance is lead;
[0103] In this embodiment, the insulating sheath and the insulator are made of modified ABS-PP, the tensile strength (test standard ISO527) of the modified ABS-PP is 27.10 MPa, the bending strength (test standard ISO178) is 37.3 MPa, and the melt index (test standard ISO1133) is 2.2 g / 10 min at 230°C / 2.16 kg.
[0104] In this embodiment, the fixing frame between the anode composite rods is die-cast by a die-casting machine, and its composition is a lead-tin-bismuth alloy, in which the mass percentage of tin in the alloy is 2.5%, the mass percentage of bismuth is 1.5%, and the balance is lead;
[0105] In this embodiment, the titanium sponge particles in the α-PbO2 / active titanium sponge particle composite layer (thickness of 500 μm) are cone-shaped, the particle size of the titanium sponge particles is 10 μm, and the proportion of the titanium sponge particles in the composite coating is 10 wt%.
[0106] The preparation method of the fence-type stainless steel-based composite anode plate for copper electrowinning has the following steps:
[0107] (1) Preparation of copper-clad stainless steel tube conductive beam coated with lead alloy: First, the stainless steel tube is degreased and activated. In a 20% by mass NaOH + 8% Na2CO3 solution, the temperature is controlled at 40°C and degreased for 8 minutes. Then, it is immediately washed with water, and then immersed in a 10% by mass HCl solution for activation for 1 minute. The temperature is controlled at 35°C and washed with deionized water. Then, the outer wall of the treated stainless steel tube is compounded with the inner wall of the dried copper tube treated with 5% HNO3 activation (activation temperature is 60°C, activation time is 1 minute) and extruded and drawn at a speed of 8m / min to obtain a copper-clad stainless steel tube processed into a U-shaped conductive beam structure. Then, the copper surface of the copper-clad stainless steel tube conductive beam is degreased and activated. In a 10% by mass NaOH solution, the copper surface of the copper-clad stainless steel tube conductive beam is degreased and activated. , control the temperature at 60°C, degrease for 5 minutes, then immediately rinse with water, and then immerse in 10% HNO3 by mass fraction for activation for 1 minute, control the temperature at 60°C, and rinse with deionized water; then place the treated copper-clad stainless steel tube in an oven and control the temperature at 120°C for drying time for 5 minutes, immediately put it into the molten lead-tin-antimony rare earth alloy liquid and control the temperature at 450°C to move the conductive beam up and down for hot dip plating for 1 minute, repeat the dip plating twice to obtain a copper-clad stainless steel tube conductive beam coated with lead-tin-antimony rare earth alloy; finally, put the treated copper-clad stainless steel tube conductive beam into a die-casting mold, pour the antimony-lead alloy liquid, and perform die-casting to obtain a copper-clad stainless steel tube conductive beam coated with lead alloy; the mass percentage of antimony in the antimony-lead alloy liquid is 2.5%, and the mass percentage of tin is 2.5%;
[0108] (2) Preparation of anode composite rod: The stainless steel tube was degreased and activated in a solution of 8% NaOH + 5% Na2CO3 at a temperature of 60°C for 5 min, then immediately rinsed with water, and then immersed in a solution of 5% HCl for activation for 2 min at a temperature of 30°C, and then rinsed with deionized water;
[0109] (3) The stainless steel tube treated in step (2) was placed in a nickel plating solution for electroplating for 5 min, with the temperature and current density controlled at 25° C. and 4 A / dm 2 , washed with deionized water, the nickel plating solution formula is: nickel chloride 180g / L, 37wt% hydrochloric acid 80ml / L, ethylenediaminetetraacetic acid disodium 8g / L;
[0110] (4) The nickel-plated stainless steel tube in step (3) was placed in a copper-tin alloy solution for electroplating for 30 minutes, with the temperature and current density controlled at 30°C and 1A / dm 2 , washed with deionized water and dried, the copper-tin alloy plating solution formula is 150g / L potassium pyrophosphate, 10g / L copper pyrophosphate, 8g / L sodium stannate, 30g / L potassium sodium tartrate, 0.005g / L PVP, pH = 10;
[0111] (5) placing the stainless steel tube obtained in step (4) in a drawing and extrusion machine at a speed of 12 m / min, controlling the drawing die temperature at 210° C., coating the molten high calcium lead alloy on the surface of the nickel-copper-tin alloy of the stainless steel tube by drawing and extrusion, and then cooling the obtained stainless steel tube high calcium lead alloy to room temperature by a silicone oil refrigerator, and shearing it into a plurality of stainless steel tube lead alloy rods of the same size as required;
[0112] (6) The stainless steel-based lead alloy rod obtained in step (5) is cleaned with 10 g / L lead acetate and 100 g / L acetic acid solution and deionized water, and then a composite electrodeposition of α-PbO2 / active sponge titanium particles is performed on the outer surface to obtain a stainless steel-based lead alloy / α-PbO2 / active sponge titanium particles composite anode rod;
[0113] (7) Preparation of a fence-type composite anode plate: first, assemble the composite anode rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other using a fixing frame, and fix the left and right sides of the fence-type anode plate support with an insulating sheath, then weld the stainless steel tube in the conductive beam to the stainless steel tube of the fence-type anode plate below, then weld the lead alloy layer on the conductive beam to the high-calcium lead alloy layer on the copper rod, and finally install an insulator on the plate surface to obtain a fence-type composite anode plate;
[0114] The above-mentioned α-PbO2 / active sponge titanium particle composite layer is prepared by composite electrodeposition, and the specific process is as follows: (1) Preparation of active sponge titanium particles: It is prepared by polymer sol-gel method and thermal decomposition. Specifically, the sponge titanium particles are first placed in a 25% NaOH solution for ultrasonic degreasing, and then placed in a 25wt% hydrochloric acid solution for activation at 60°C for 5 minutes. The activated sponge titanium particles are placed in a solution with a molar ratio of M (ruthenium chloride, stannous chloride and cobalt chloride): citric acid: ethylene glycol = 1:8:30 and ultrasonically dispersed for 0.5 hours, wherein the molar ratio of ruthenium chloride: stannous chloride: cobalt chloride = 10:50:10. The filtered particles are dried at 120°C for 10 minutes, sintered at 450°C for 10 minutes, air-cooled to room temperature, and coated 10 times to control the ruthenium oxide coating loading to 1g / m 2 , and finally sintered for 0.5h to obtain active titanium sponge particles;
[0115] (2) The above active titanium sponge particles were added to an alkaline lead solution and subjected to composite electrodeposition for 0.5 h, with the temperature and current density controlled at 60 °C and 1 A / dm 2 , washed with deionized water, the solution formula is: lead oxide 40g / L, sodium hydroxide 100g / L, tartaric acid 10g / L, potassium dichromate 10g / L, gelatin 0.5g / L, active sponge titanium particles 2g / L.
[0116] The fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this example was placed in a copper electrolyte. The electrolysis conditions were: electrolyte copper ion concentration of 60 g / L, sulfuric acid concentration of 200 g / L, electrolyte temperature of 40°C, iron ion concentration of 1 g / L, Cl - Ions 20mg / L, current density 400A / m 2 ; The results show that the fence-type stainless steel-based composite anode plate has an electrical efficiency of 88%, a cell voltage of 1.89V, and a service life of 4 years. The conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate has an electrical efficiency of 86%, a cell voltage of 2.12V, and a service life of 2 years under the same working conditions. It can be seen that compared with the conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate, the fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this embodiment has an electrical efficiency increased by 2%, a cell voltage reduced by 230mV, and a service life extended by 2 times.
[0117] Example 2
[0118] This embodiment provides a Figure 1 The fence-type stainless steel-based composite anode plate for copper electrowinning of the structure shown comprises a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator; the conductive beam is composed of a stainless steel tube, a copper layer arranged on the surface of the stainless steel tube and a first lead alloy layer arranged on the surface of the copper layer; the fence-type anode plate bracket is vertically connected to the conductive beam; the fence-type anode plate bracket is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer; the fixing frame is vertically connected to the fence-type anode plate bracket; the insulating sheath is arranged parallel to the edge side of the fence-type anode plate bracket; the insulator is arranged at the lower part of the fence-type anode plate bracket to fix the lower part of the fence-type anode plate bracket.
[0119] In this embodiment, the material of the stainless steel tube is 316L, the outer surface of the stainless steel tube is tapped, the depth of the thread is 0.3mm, the cross section of the stainless steel tube is a hollow ellipse; the long axis of the inner wall is 10mm, the short axis is 1mm, the tube thickness is 2mm; the thickness of the copper layer is 3mm;
[0120] In this embodiment, the first lead alloy layer is sequentially: a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer arranged on the surface of the copper-clad stainless steel tube; the thickness of the lead-tin-antimony rare earth alloy layer is 10 μm, the content of tin in the lead-tin-antimony rare earth alloy layer is 2wt%, the content of antimony is 0.5wt%, the content of rare earth cerium (Ce) is 0.001wt%, and the balance is lead; the thickness of the first lead alloy layer is 2mm; the lead alloy in the antimony-containing lead alloy layer is a lead-tin-antimony alloy, the content of tin in the alloy layer is 0.8wt%, the content of antimony is 2.5wt%, and the balance is lead;
[0121] In this embodiment, the second lead alloy layer is sequentially: a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer arranged on the surface of the base stainless steel tube; the thickness of the nickel layer is 6 μm, the thickness of the copper-tin alloy layer is 60 μm, and the thickness of the second lead alloy layer is 1 mm; the high-calcium lead alloy in the high-calcium lead alloy layer is lead-calcium-tin, wherein the mass percentage of calcium in the high-calcium lead alloy is 0.1wt%, the mass percentage of tin in the high-calcium lead alloy is 1.0wt%, and the balance is lead;
[0122] In this embodiment, the insulating sheath and the insulator are made of modified PE-PP, the tensile strength (test standard ISO527) of the modified PE-PP is 27.10MPa, the bending strength (test standard ISO178) is 37.3MPa, the melt index (test standard ISO1133) is 2.2g / 10min under 230℃ / 2.16kg conditions, and the cantilever beam notched impact strength (test standard ISO180) is 52.6KJ / m 2 ;
[0123] In this embodiment, the fixing frame between the anode composite rods is die-cast by a die-casting machine, and its composition is a lead-tin-antimony alloy, in which the mass percentage of tin in the alloy is 0.6%, the mass percentage of antimony is 0.8%, and the balance is lead;
[0124] In this embodiment, the titanium sponge particles in the α-PbO2 / active titanium sponge particle composite layer (thickness of 100 μm) are cone-shaped, the particle size of the titanium sponge particles is 0.1 μm, and the proportion of the titanium sponge particles in the composite coating is 0.5 wt %.
[0125] The preparation method of the fence-type stainless steel-based composite anode plate for copper electrowinning has the following steps:
[0126] (1) Preparation of copper-clad stainless steel tube conductive beam coated with lead alloy: First, the stainless steel tube is degreased and activated. In a solution of 8% by mass NaOH + 10% Na2CO3, the temperature is controlled at 50°C for degreasing for 10 minutes, and then it is immediately washed with water, and then immersed in a solution of 10% by mass HCl for activation for 1 minute, the temperature is controlled at 25°C, and it is washed with deionized water; then the outer wall of the treated stainless steel tube is compounded with the inner wall of the dried copper tube treated with 5% HNO3 activation (activation temperature is 40°C, activation time is 5 minutes) and extruded and drawn at a speed of 2m / min to obtain a copper-clad stainless steel tube processed into a U-shaped conductive beam structure; then the copper surface of the copper-clad stainless steel tube conductive beam is degreased and activated in a solution of 8% by mass NaOH. , control the temperature at 70°C, degrease for 50 minutes, then immediately rinse with water, and then immerse in 15% HNO3 by mass fraction for activation for 2 minutes, control the temperature at 60°C, and rinse with deionized water; then place the treated copper-clad stainless steel pipe in an oven and control the temperature at 100°C for drying time for 10 minutes, immediately put it into a molten lead-tin-antimony rare earth alloy liquid and control the temperature at 400°C to move the conductive beam up and down for hot dip plating for 1 minute, repeat the dip plating twice to obtain a copper-clad stainless steel pipe conductive beam coated with lead-tin-antimony rare earth alloy; finally, put the treated copper-clad stainless steel pipe conductive beam into a die-casting mold, pour the antimony-lead alloy liquid, and perform die-casting to obtain a copper-clad stainless steel pipe conductive beam coated with lead alloy; the mass percentage of antimony in the antimony-lead alloy liquid is 5%, and the mass percentage of tin is 0.5%;
[0127] (2) Preparation of anode composite rod: The stainless steel tube was degreased and activated in a solution of 8% NaOH + 5% Na2CO3 at a temperature of 60°C for 5 min, then immediately rinsed with water, and then immersed in a solution of 5% HCl for activation for 2 min at a temperature of 30°C, and then rinsed with deionized water;
[0128] (3) The stainless steel tube treated in step (2) was placed in a nickel plating solution for electroplating for 5 minutes, and the temperature and current density were controlled at 25°C and 2A / dm 2 , washed with deionized water, the nickel plating solution formula is: nickel chloride 180g / L, 37wt% hydrochloric acid 80ml / L, ethylenediaminetetraacetic acid disodium 8g / L;
[0129] (4) Plating the nickel-plated stainless steel tube in step (3) in a copper-tin alloy solution for electroplating for 30 minutes, with the temperature and current density controlled at 20° C. and 1 A / dm 2 , washed with deionized water and dried, the copper-tin alloy plating solution formula is 150g / L potassium pyrophosphate, 10g / L copper pyrophosphate, 8g / L sodium stannate, 30g / L potassium sodium tartrate, 0.005g / L PVP, pH = 10;
[0130] (5) placing the stainless steel tube obtained in step (4) in a drawing and extrusion machine at a speed of 10 m / min, controlling the temperature of the drawing die at 210° C., coating the molten high-calcium lead alloy on the surface of the nickel-copper-tin alloy of the stainless steel tube by drawing and extrusion, and then cooling the obtained stainless steel tube high-calcium lead alloy to room temperature by a silicone oil refrigerator, and shearing it into a plurality of stainless steel tube lead alloy rods of the same size as required;
[0131] (6) The stainless steel-based lead alloy rod obtained in step (5) is cleaned with 30 g / L lead acetate and 10 g / L acetic acid solution and deionized water, and then a composite electrodeposition of α-PbO2 / active sponge titanium particles is performed on the outer surface to obtain a stainless steel-based lead alloy / α-PbO2 / active sponge titanium particles composite anode rod;
[0132] (7) Preparation of a fence-type composite anode plate: first, assemble the composite anode rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other using a fixing frame, and fix the left and right sides of the fence-type anode plate support with an insulating sheath, then weld the stainless steel tube in the conductive beam to the stainless steel tube of the fence-type anode plate below, then weld the lead alloy layer on the conductive beam to the high-calcium lead alloy layer on the copper rod, and finally install an insulator on the plate surface to obtain a fence-type composite anode plate;
[0133] The above-mentioned α-PbO2 / active sponge titanium particle composite layer is prepared by composite electrodeposition, and the specific process is as follows: (1) Preparation of active sponge titanium particles: It is prepared by polymer sol-gel method and thermal decomposition. Specifically, the sponge titanium particles are first placed in a 20% NaOH solution for ultrasonic degreasing, and then placed in a 20wt% hydrochloric acid solution for activation at 60°C for 5 minutes. The activated sponge titanium particles are placed in a solution with a molar ratio of M (ruthenium chloride, stannous chloride and cobalt chloride): citric acid: ethylene glycol = 2:3:10 and ultrasonically dispersed for 0.5 hours, wherein the molar ratio of ruthenium chloride: stannous chloride: cobalt chloride = 20:50:30. The filtered particles are dried at 120°C for 10 minutes, sintered at 400°C for 5 minutes, air-cooled to room temperature, and repeated for 8 times to control the ruthenium oxide coating loading to 1g / m 2 , and finally sintered for 0.5h to obtain active titanium sponge particles;
[0134] (2) The above-mentioned active titanium sponge particles were added to an alkaline lead solution and subjected to composite electrodeposition for 0.5 h, with the temperature and current density controlled at 20 °C and 1 A / dm 2 , washed with deionized water, the solution formula is: lead oxide 40g / L, sodium hydroxide 100g / L, tartaric acid 10g / L, potassium dichromate 0.5g / L, PVP 0.01g / L, active sponge titanium particles 3g / L.
[0135] The fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this example was placed in a copper electrolyte. The electrolysis conditions were: electrolyte copper ion concentration of 60 g / L, sulfuric acid concentration of 200 g / L, electrolyte temperature of 40°C, iron ion concentration of 1 g / L, Cl - Ions 20mg / L, current density 200A / m 2 ; The results show that the fence-type stainless steel-based composite anode plate has an electrical efficiency of 92%, a cell voltage of 1.59V, and a service life of 7.5 years. The conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate has an electrical efficiency of 89%, a cell voltage of 1.92V, and a service life of 3 years under the same working conditions. It can be seen that compared with the conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate, the fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this embodiment has an electrical efficiency increased by 3%, a cell voltage reduced by 330mV, and a service life extended by 2.5 times.
[0136] Example 3
[0137] This embodiment provides a Figure 1 The fence-type stainless steel-based composite anode plate for copper electrowinning of the structure shown comprises a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator; the conductive beam is composed of a stainless steel tube, a copper layer arranged on the surface of the stainless steel tube and a first lead alloy layer arranged on the surface of the copper layer; the fence-type anode plate bracket is vertically connected to the conductive beam; the fence-type anode plate bracket is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer; the fixing frame is vertically connected to the fence-type anode plate bracket; the insulating sheath is arranged parallel to the edge side of the fence-type anode plate bracket; the insulator is arranged at the lower part of the fence-type anode plate bracket to fix the lower part of the fence-type anode plate bracket.
[0138] In this embodiment, the material of the stainless steel tube is 316L, the outer surface of the stainless steel tube is tapped, the depth of the thread is 0.3mm, the cross section of the stainless steel tube is a hollow ellipse; the major axis of the inner wall is 20mm, the minor axis is 8mm, the tube thickness is 4mm; the thickness of the copper layer is 4mm;
[0139] In this embodiment, the first lead alloy layer is sequentially: a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer arranged on the surface of the copper-clad stainless steel tube, the thickness of the lead-tin-antimony rare earth alloy layer is 80 μm, the content of tin in the lead-tin-antimony rare earth alloy layer is 5wt%, the content of antimony is 1wt%, the content of rare earth neodymium (Nd) is 0.06wt%, and the balance is lead; the thickness of the first lead alloy layer is 4 mm; the lead alloy in the antimony-containing lead alloy layer is a lead-silver-tin-antimony alloy, the content of tin in the alloy layer is 0.8wt%, the content of antimony is 2.8wt%, the content of silver is 0.03wt%, and the balance is lead;
[0140] In this embodiment, the second lead alloy layer is sequentially: a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer arranged on the surface of the base stainless steel tube; the thickness of the nickel layer is 8 μm, the thickness of the copper-tin alloy layer is 120 μm, and the thickness of the second lead alloy layer is 3 mm; the high-calcium lead alloy in the high-calcium lead alloy layer is lead-calcium-tin, wherein the mass percentage of calcium in the high-calcium lead alloy is 0.8%, the mass percentage of tin in the high-calcium lead alloy is 1.8%, and the balance is lead;
[0141] In this embodiment, the insulating sheath and the insulator are made of modified PVC-PP, and the tensile strength (test standard ISO527) of the modified PVC-PP is 22.10MPa, the bending strength (test standard ISO178) is 47.3MPa, the melt index (test standard ISO1133) is 2.8g / 10min under 230℃ / 2.16kg conditions, and the cantilever beam notched impact strength (test standard ISO180) is 46.6KJ / m 2 ;
[0142] In this embodiment, the fixing frame between the anode composite rods is die-cast by a die-casting machine, and its composition is a lead-tin-antimony rare earth alloy, in which the mass percentage of tin in the alloy is 0.5%, the mass percentage of antimony is 0.8%, the mass percentage of rare earth cerium (Ce) is 0.06%, and the balance is lead;
[0143] In this embodiment, the titanium sponge particles in the α-PbO2 / active titanium sponge particle composite layer (thickness of 200 μm) are cone-shaped, the particle size of the titanium sponge particles is 1 μm, and the proportion of the titanium sponge particles in the composite coating is 6 wt %.
[0144] The preparation method of the fence-type stainless steel-based composite anode plate for copper electrowinning has the following steps:
[0145] (1) Preparation of copper-clad stainless steel tube conductive beam coated with lead alloy: First, the stainless steel tube is degreased and activated. In a 10% NaOH + 2% Na2CO3 solution, the temperature is controlled at 60°C for 20 minutes, and then it is immediately washed with water. Then, it is immersed in a 10% HCl solution for activation for 3 minutes, the temperature is controlled at 35°C, and it is washed with deionized water. Then, the outer wall of the treated stainless steel tube is compounded with the inner wall of the dried copper tube treated with 10% HNO3 activation (activation temperature is 30°C, activation time is 8 minutes), and extrusion and drawing are performed at a speed of 6m / min to obtain the copper-clad stainless steel tube. The copper surface of the copper-clad stainless steel tube conductive beam is degreased and activated. In a 8% NaOH solution, the copper surface of the copper-clad stainless steel tube conductive beam is heated to 100°C and then heated to 80°C. The temperature is controlled at 70°C, and degreasing is performed for 30 minutes. Then, the tube is immediately washed with water, and then immersed in 10% HNO3 by mass fraction for activation for 6 minutes. The temperature is controlled at 20°C, and the tube is washed with deionized water. Then, the treated copper-clad stainless steel tube is placed in an oven and the temperature is controlled at 120°C for drying for 20 minutes. The tube is immediately placed in a molten lead-tin-antimony rare earth alloy liquid and the conductive beam is moved up and down at a temperature of 450°C for hot dip plating for 3 minutes. The dipping is repeated 4 times to obtain a copper-clad stainless steel tube conductive beam coated with lead-tin-antimony rare earth alloy. Finally, the treated copper-clad stainless steel tube conductive beam is placed in a die-casting mold, and antimony-lead alloy liquid is poured and die-casted to obtain a copper-clad stainless steel tube conductive beam coated with lead alloy. The mass percentage of antimony in the antimony-lead alloy liquid is 3%, and the mass percentage of tin is 1%.
[0146] (2) Preparation of anode composite rod: The stainless steel tube was degreased and activated in a 10% NaOH + 5% Na2CO3 solution at 70°C for 10 min, then immediately rinsed with water, and then immersed in 20% HCl for activation for 1 min at 35°C, and then rinsed with deionized water;
[0147] (3) The stainless steel tube treated in step (2) was placed in a nickel plating solution for electroplating for 15 minutes, and the temperature and current density were controlled at 35°C and 4A / dm 2 , washed with deionized water, the nickel plating solution formula is: nickel chloride 200g / L, 37wt% hydrochloric acid 100ml / L, ethylenediaminetetraacetic acid disodium 16g / L;
[0148] (4) The nickel-plated stainless steel tube in step (3) was placed in a copper-tin alloy solution for electroplating for 50 minutes, with the temperature and current density controlled at 40°C and 2A / dm 2 , washed with deionized water and dried, the copper-tin alloy plating solution formula is potassium pyrophosphate 180g / L, copper pyrophosphate 30g / L, sodium stannate 8g / L, potassium sodium tartrate 50g / L, PVP 0.005g / L, pH = 10;
[0149] (5) placing the stainless steel tube obtained in step (4) in a drawing and extrusion machine at a speed of 6 m / min, controlling the drawing die temperature at 190° C., coating the molten high calcium lead alloy on the surface of the nickel-copper-tin alloy of the stainless steel tube by drawing and extrusion, and then cooling the obtained stainless steel tube high calcium lead alloy to room temperature by a silicone oil refrigerator, and shearing it into a plurality of stainless steel tube lead alloy rods of the same size as required;
[0150] (6) The stainless steel-based lead alloy rod obtained in step (5) is cleaned with 60 g / L lead acetate and 20 g / L acetic acid solution and deionized water, and then a composite electrodeposition of α-PbO2 / active sponge titanium particles is performed on the outer surface to obtain a stainless steel-based lead alloy / α-PbO2 / active sponge titanium particles composite anode rod;
[0151] (7) Preparation of a fence-type composite anode plate: first, assemble the composite anode rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other using a fixing frame, and fix the left and right sides of the fence-type anode plate support with an insulating sheath, then weld the stainless steel tube in the conductive beam to the stainless steel tube of the fence-type anode plate below, then weld the lead alloy layer on the conductive beam to the high-calcium lead alloy layer on the copper rod, and finally install an insulator on the plate surface to obtain a fence-type composite anode plate;
[0152] The above-mentioned α-PbO2 / active sponge titanium particle composite layer is prepared by composite electrodeposition, and the specific process is as follows: (1) Preparation of active sponge titanium particles: It is prepared by polymer sol-gel method and thermal decomposition. Specifically, the sponge titanium particles are first placed in a 20% NaOH solution for ultrasonic degreasing, and then placed in a 20wt% hydrochloric acid solution for activation at 20°C for 8 minutes. The activated sponge titanium particles are placed in a solution with a molar ratio of M (ruthenium chloride, stannous chloride and cobalt chloride): citric acid: ethylene glycol = 5:6:20 and ultrasonically dispersed for 1 hour, wherein the molar ratio of ruthenium chloride: stannous chloride: cobalt chloride = 30:40:30. The filtered particles are dried at 120°C for 10 minutes, sintered at 500°C for 10 minutes, air-cooled to room temperature, and repeated for 10 times to control the ruthenium oxide coating loading to 3g / m 2 , and finally sintered for 1h to obtain active titanium sponge particles;
[0153] (2) The above-mentioned active titanium sponge particles were added to an alkaline lead solution and subjected to composite electrodeposition for 2 h, with the temperature and current density controlled at 40 °C and 1 A / dm 2 , washed with deionized water, the solution formula is: lead oxide 50g / L, sodium hydroxide 180g / L, tartaric acid 20g / L, potassium dichromate 5g / L, OP emulsifier 0.3g / L, active sponge titanium particles 8g / L.
[0154] The fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this example was placed in a copper electrolyte. The electrolysis conditions were: electrolyte copper ion concentration of 60 g / L, sulfuric acid concentration of 200 g / L, electrolyte temperature of 40°C, iron ion concentration of 1 g / L, Cl - Ions 20mg / L, current density 400A / m 2 ; The results show that the fence-type stainless steel-based composite anode plate has an electrical efficiency of 94%, a cell voltage of 1.52V, and a service life of 9 years. The conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate has an electrical efficiency of 89%, a cell voltage of 1.92V, and a service life of 3 years under the same working conditions. It can be seen that compared with the conventional Pb-0.06wt%Ca-1.2wt%Sn anode plate, the fence-type stainless steel-based composite anode plate for copper electrowinning prepared in this embodiment has an electrical efficiency increased by 5%, a cell voltage reduced by 400mV, and a service life extended by 3 times.
[0155] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A fence-type stainless steel-based composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate bracket, a fixing frame, an insulating sheath and an insulator; The conductive beam is composed of a stainless steel tube, a copper layer disposed on the surface of the stainless steel tube, and a first lead alloy layer disposed on the surface of the copper layer; The fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a stainless steel tube, a second lead alloy layer arranged on the surface of the stainless steel tube, and an α-PbO2 / active sponge titanium particle composite layer arranged on the surface of the second lead alloy layer; the second lead alloy layer includes a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer stacked in sequence, the nickel layer is close to the surface end of the stainless steel tube; the α-PbO2 / active sponge titanium particle composite layer is composed of α-PbO2 and active sponge titanium particles, the active sponge titanium particles include sponge titanium particles and active metal oxides loaded on the surface of the sponge titanium particles, the active metal oxides include ruthenium oxide, tin oxide and cobalt oxide; The fixing frame is made of lead or lead alloy and is vertically connected to the fence-type anode plate support to fix the anode composite rod of the fence-type anode plate support; The insulating sheath is arranged parallel to the edge side of the fence type anode plate support to fix the edge of the fence type anode plate support; The insulator is arranged at the lower part of the fence type anode plate support and is used for fixing the lower part of the fence type anode plate support.
2. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 1, characterized in that: The first lead alloy layer comprises a lead-tin-antimony rare earth alloy layer and an antimony-containing lead alloy layer which are sequentially stacked, the lead-tin-antimony rare earth alloy layer being close to the surface end of the copper layer; the lead-tin-antimony rare earth alloy layer has a thickness of 8 to 100 μm, and the first lead alloy layer has a thickness of 0.1 to 10 mm; The thickness of the nickel layer is 6-10 μm, the thickness of the copper-tin alloy layer is 60-200 μm; and the thickness of the second lead alloy layer is 1-6 mm.
3. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 1, characterized in that: The high calcium lead alloy in the high calcium lead alloy layer is selected from one of lead calcium alloy, lead calcium tin alloy, lead calcium tin rare earth alloy, lead calcium tin aluminum rare earth alloy and lead calcium silver tin rare earth alloy; the mass percentage of calcium in the high calcium lead alloy is 0.1-5wt%.
4. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 2, characterized in that: The lead-tin-antimony rare earth alloy layer contains 1-7wt% tin, 0.5-3wt% antimony, 0.001-0.08wt% rare earth and the balance is lead.
5. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 1, characterized in that: The active titanium sponge particles in the α-PbO2 / active titanium sponge particle composite layer are in the shape of a cone or a rod; the particle size of the active titanium sponge particles is 0.1 to 10 μm; and the content of the active titanium sponge particles in the composite layer is 0.5 to 10 wt%.
6. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 1, characterized in that: In the conductive beam and the anode composite rod, the outer surface of the stainless steel tube has a thread, and the depth of the thread is 0.3 to 1.2 mm; the cross-section of the stainless steel tube is a hollow isomeric circular shape, a hollow isomeric square shape, a hollow isomeric rectangular shape or a hollow elliptical shape; the long axis of the inner wall of the cross-section of the stainless steel tube is 2 to 20 mm long, and the short axis is 1 to 8 mm long; the material of the stainless steel tube is 304 stainless steel or 316L stainless steel; the tube thickness of the stainless steel tube is 2 to 6 mm.
7. The fence-type stainless steel-based composite anode plate for copper electrowinning according to claim 1, characterized in that: The insulating sheath and the insulator are made of modified PE-PP, modified PVC-PP or modified ABS-PP; The material of the fixing frame is selected from one of lead-tin-antimony alloy, lead-tin-antimony rare earth alloy and lead-tin-antimony-strontium rare earth alloy.
8. A method for preparing the fence-type stainless steel-based composite anode plate for copper electrodeposition according to claim 1, comprising the following steps: A) activating a stainless steel tube, then coating a copper layer on the surface of the activated stainless steel tube, then activating the copper layer, and then coating a first lead alloy layer on the surface of the activated copper layer to obtain a conductive beam; B) activating the stainless steel tube, coating the outer surface of the activated stainless steel tube with a second lead alloy layer, and then electro-depositing an α-PbO2 / active sponge titanium particle composite layer on the surface of the second lead alloy layer to obtain an anode composite rod; wherein the second lead alloy layer comprises a nickel layer, a copper-tin alloy layer and a high-calcium lead alloy layer stacked in sequence, and the nickel layer is close to the surface end of the stainless steel tube; the α-PbO2 / active sponge titanium particle composite layer comprises α-PbO2 and active sponge titanium particles, and the active sponge titanium particles comprise sponge titanium particles and active metal oxides loaded on the surface of the sponge titanium particles, and the active metal oxides comprise ruthenium oxide, tin oxide and cobalt oxide; Assembling a plurality of the anode composite rods into a fence shape to obtain a fence-shaped anode plate support; The anode composite rods of the fence-type anode plate support are fixed by a fixing frame, and the edge side of the fence-type anode plate support is fixed by an insulating sheath to obtain an integral fence-type anode plate support; There is no order of precedence between step A) and step B); C) connecting the conductive beam obtained in step A) with the integral fence-type anode plate support obtained in step B), and installing an insulator at the bottom of the fence-type anode plate support to obtain a fence-type stainless steel-based composite anode plate for copper electrodeposition.
9. The preparation method according to claim 8, characterized in that: In step A), the coating process of the first lead alloy layer specifically includes: Placing the activated copper-clad stainless steel tube in a lead-tin-antimony rare earth alloy liquid for hot-dip plating; the temperature of the lead-tin-antimony rare earth alloy liquid is 400-600° C., and the hot-dip plating time is 0.1-8 min; Placing the hot-dip plated copper-clad stainless steel tube in a die-casting mold, pouring antimony-containing lead alloy liquid and die-casting to obtain a first lead alloy layer; In step B), the coating process of the second lead alloy layer specifically includes: The activated stainless steel tube is placed in a nickel plating solution for electroplating; the nickel plating solution comprises: 180-250 g / L nickel chloride, 80-120 ml / L hydrochloric acid, and 8-20 g / L disodium ethylenediaminetetraacetate; the cathode current density of the electroplating is 2-5 A / dm 2 The electroplating temperature is 25 to 45° C., and the electroplating time is 1 to 20 minutes; The nickel-plated stainless steel tube is placed in a copper-tin alloy plating solution for secondary electroplating; the copper-tin alloy plating solution comprises: 150-200 g / L potassium pyrophosphate, 10-30 g / L copper pyrophosphate, 8-20 g / L sodium stannate, 30-60 g / L potassium sodium tartrate, and 0.005-0.02 g / L PVP; the cathode current density of the secondary electroplating is 1-3 A / dm 2 The temperature of the secondary electroplating is 20 to 50° C., and the time of the secondary electroplating is 20 to 60 minutes; The copper-tin alloy-plated stainless steel tube is placed in a drawing and extrusion machine, and the semi-molten high-calcium lead alloy is coated by drawing and extrusion, and then cooled to obtain a second lead alloy layer.
10. The preparation method according to claim 8, characterized in that: In step B), the preparation process of the α-PbO2 / active titanium sponge particle composite layer specifically includes: The stainless steel tube wrapped with the second lead alloy layer is placed in an alkaline lead solution for electrodeposition to obtain an α-PbO2 / active sponge titanium particle composite layer; the alkaline lead solution comprises: 40-60 g / L lead oxide, 100-180 g / L sodium hydroxide, 10-40 g / L tartaric acid, 0.1-10 g / L potassium dichromate, 0.01-0.5 g / L surfactant, and 2-10 g / L active sponge titanium particles; the anode current density of the electrodeposition is 1-3 A / dm 2 , the electrodeposition temperature is 20 to 50° C., and the electrodeposition time is 0.5 to 3 hours; The active titanium sponge particles are prepared according to the following steps: The sponge titanium particles are placed in a hydrochloric acid solution for activation, and then the activated sponge titanium particles are placed in an active substance solution for ultrasonic dispersion, filtration, drying, and sintering to obtain active sponge titanium particles; the concentration of the hydrochloric acid solution is 15-25wt%; the activation temperature is 60-80°C, and the activation time is 5-30min; the active substance solution contains active metal compounds, citric acid and ethylene glycol, the active metal compounds include ruthenium chloride, stannous chloride and cobalt chloride, and the molar ratio of the ruthenium chloride, stannous chloride and cobalt chloride is The molar ratio of the active metal compound, citric acid and ethylene glycol is (1-5): (3-8): (10-30); the ultrasonic dispersion time is 0.5-2h; the drying temperature is 100-150°C, and the drying time is ≥10min; the sintering temperature is 400-600°C, and the sintering time is 5-50min; the ruthenium oxide loading on the surface of the active titanium sponge particles is 1-3g / m 2 .
Citation Information
Patent Citations
Fence type titanium-based PbO2 anode for electrodeposition of non-ferrous metals and manufacturing method of anode
CN103572331A
Fence-shaped composite anode plate used for copper electro-deposition and preparation method thereof
CN108823603A